A mixed method study on the metacognitive awareness of reading strategies used by Saudi EFL students - Mohammad H. Al-khresheh; Rim Al Basheer Ben Ali (Journal of Pedagogical Research, 2023)
Metacognitive awareness of reading strategy has a significant impact on language learning. It addresses how students organize context-based interactions and how they may employ reading comprehension strategies. Saudi students of English still face reading comprehension issues that significantly affect their overall language learning. Therefore, this mixed method study sought to assess Saudi English students’ metacognitive awareness of reading strategies, determine whether gender and university level affect their use of these strategies, and explore English instructors’ views on this issue. Two instruments were used to achieve these objectives. Two hundred ten students were surveyed for quantitative data. 15 English instructors were interviewed in a semi-structured manner for qualitative data. Descriptive statistical analysis was used to analyze the quantitative data gathered, while pattern matching and thematic content analysis were applied to analyze the qualitative data. The results demonstrated that Saudi EFL students’ metacognitive awareness of reading methods was generally moderate. This awareness was moderate regarding the use of global reading strategies and low regarding support and problem-solving strategies. The metacognitive awareness levels for global strategies vary significantly by gender, in favour of females. Senior and junior university students had better global and support reading methods than freshmen. The qualitative data from the interview supported the quantitative data suggesting Saudi EFL students had low to moderate metacognitive awareness. Their low-to-moderate level explains their poor reading comprehension. Based on these findings, limitations and recommendations are given.